Ocular Surface Microbiome Transplantation In Dogs: Treat To Target On ‘Gut-Eye Axis’: Gut-Eye Axis-Based Ocular Microbiome Therapy in Dogs - Ural, Kerem; Erdogan, Hasan; Erdogan, Songül; Pasa, Serdar; Ozalp, Tahir (Jurnal Agro Veteriner, 2025)
The ocular surface microbiome (osum) is an organized group of microorganisms along with owned genes residing on eye surface. The latter collection is a normal trait for eye health with a participant protection role. In the present original article of prospective case series the presenting author aimed at reporting natural treatment with osum, as because of microbiome modulation of ‘treat to target’ purpose. Given disadvantages of drugs used in ophthalmology, and based on selected probiotic strains with a very limited choices, presenting author decided to change ocular surface microechology by transferring microbiome from healthy donors to diseased 7 dogs. Canine allergic conjunctivitis (n=3), n=1 each for Canine Visceral Leishmaniasis co-morbidity infectious ulcerative keratitis, keratoconjunctivitis sicca, Canine Monocytic Ehrlichiosis related infectious ulcerative keratitis and vision loss were entire problem list. On every session a healthy donor was selected and used for transfer of ocular surface microbiome by use of sterile cotton swab.Complete recovery (n=3) and partial recovery (n=1) were evident out of 7 dogs enrolled. This natural treatment modality, unless this technique was developed by the presenting author, could substitute drug usage at least for canine allergic conjunctivitis along with microbiome modulation